THE EFFECTIVENESS OF USING CONTEXTUAL TEACHING AND LEARNING (CTL) APPROACH IN IMPROVING TEACHING AND LEARNING ENGLISH - Nenden Muni Anggarini, - (2008)
This quasi-experimental study entitled THE EFFECTIVENESS OF USING CONTEXTUAL TEACHING AND LEARNING (CTL) APPROACH IN IMPROVING TEACHING AND LEARNING ENGLISH (An Experimental Research in the First Grade Students of SMP 1 Kadungora Garut) supervised by Dr. Yoyo Surjakusumah, M.Pd. as the first supervisor and Budi Hermawan, S.Pd., M.P.C. as the second supervisor, with the non• equivalent control group design investigated the effectiveness of the Contextual Teaching and Leaming (CTL) approach in improving the students' English achievement. It was assumed that the CTL approach was not effective in improving students' English achievement. This study involved 82 first grade students at SMPN 1 Kadungora Garut, which divided into two groups: experimental and control groups. Both groups received pretest before and posttest after receiving different treatments. The experimental received teaching English using the CTL approach and the control group received teaching English without the CTL approach. The questionnaire and interview concerning the CTL approach used in Engtish lesson were also given to the experimental group to find out to what extend the CTL approach is effective in teaching English. The result of the data analysis for pretest and posttest score of both groups showed that lobs for experimental group was lower than lcrit (-7.423 < -2.021) and lobs for control group was higher than lcr;, (-1.121 > -2.021), which mean the CTL approach was more effective in improving the students' English achievement. The result of the post-test score analysis also shows that two groups had different improvement. The significance of the different was found by calculating the students' progress in English achievement (gain) showing that the experimental group's gain was 24.74% higher than the control group's.